OBSERVASI PENURUNAN TEKANAN (PRESSURE DROP) PADA SISTEM PERPIPAAN: PENGARUH PANJANG DAN DIAMETER PIPA, ELBOW, DAN TEE - Nuryoto, Nuryoto; Rahmayetty, Rahmayetty; Yusuf Rumbino; Astrilia Damayanti; Doni Rahmat Wicakso (Jurnal Rekayasa Mesin, 2024)
The piping system is a fundamental process equipment in the industry. The phenomena that occur in piping systems vary depending on the conditions of the pipes and the fluids flowing through them. Therefore, research related to piping systems requires attention to minimize and understand the occurring phenomena. There have been many studies related to piping analysis, but what sets this research apart from previous studies is that it focuses on examining the contribution of each component of the piping system to friction loss-pressure drop. Furthermore, the data obtained is used to determine the deviation or difference between experimental data and theoretical calculations. This research aims to study the correlation between friction loss and pressure drop in piping systems (including pipes, elbows, and tees) and to determine the extent of deviation between theoretical calculations and actual conditions, as well as to understand the trend of such deviations. Results show that as the length of the pipe increases, there is an increase in pressure drop, especially for pipe lengths of 0.6, 0.8, and 1.4 meters, the values are 275.26, 367.0, and 642.27 Pa over density, respectively. Conversely, as the pipe diameter increases, the resulting pressure drop becomes smaller, namely for pipe diameters of 0.5, 0.75, and 1.25 inches, the values are 266.64, 93.33, and 13.33 Pa over density, respectively. In the observation of the influence of fittings, it is shown that the pressure drop generated by elbows is greater than that of tees, with values of 26.66 and 13.33 Pa over density, respectively. When calculating the percentage deviation, there is a tendency for longer pipes and larger diameters will increase the percentage of deviation. For pipe lengths of 0.4, 0.6, and 1.4 meters, the percentage deviations are 3.23, 10.11, and 17.50%, respectively. For variations in pipe diameter, the percentage deviations are 3.23, 41.74, and 47.15% for diameters of 0.5, 0.75, and 1.25 inches, respectively. Meanwhile, the percentage deviation for tees is greater than that of elbows, with values of 84.78% (for elbows) and 185.02% (for tees).